Pendampingan Pembuatan Desain Logo Pada Kue Batang Macis Sagu Desa Tatabau: Pengabdian - Sarni Sabonak; Ade Putra Ode Amane; Firna G Gimpe; Wa Nova; Ardiansyah; Muhammad Afandi; Zulfikar; Archindra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A logo plays a crucial role as the face of a brand. Through a logo, the public can recognize a product and associate it with certain associations. In Tatabau Village, there are MSMEs (Micro, Small, and Medium Enterprises) that offer potential for economic growth. The women in Tatabau Village dominate this sector, with the majority producing processed foods. The existence of MSMEs is undeniable, as they have proven their resilience and are driving the economy, especially after the economic crisis. On the other hand, MSMEs also face numerous challenges, including limited capital and limited mastery of science and technology. One of the challenges faced by MSMEs in Tatabau Village is the lack of a logo or product identity. This is due to a lack of knowledge among MSME owners, as they are typically women who have limited digital interaction. The purpose of this community service program is to help MSMEs in Tatabau Village develop product logos to increase buyer interest and provide a distinctive product identity. The community service method includes observation, coordination with MSMEs, and implementation of community service activities. The results of the community service program have had a positive impact on increasing understanding of branding, the importance of product logos, and marketing strategies. Keywords: Mentoring, Design, MSMEs, Tatabau Village